دور سعر الصرف الأجنبي في رفع كفاءة السیاسة النقدیة - عمر ساسي, ساسي; يخلف مسعود, يوسف (جامعة الوادي - University of Eloued, 2015)
This study aims to identify a role of foreign exchange price, to increase the efficiency of monetary policy, by studying the relationship between a real exchange price & an inflation rate in Libyan economy, during 1980- 2013s . Furthermore, it was used Auto regressive distributed lag (ARDL) Model for long & short run as methodology. In additional, this study found out that, there is no relationship between an inflation rate & a real exchange rate of Libyan dinars in long run, but in short run there is a positive relationship between an inflation rate for current year & an inflation rate for 3 lags (three years ago), and also, a negative relationship with a real exchange rate for 3 lags (three years ago), so it could be statement that a real exchange rate has significant effect on monetary policy. Therefore, a Libyan Monetary Authority should be taken into account a real exchange price has ability to effect of Libyan monetary policy
Role of foreign exchange policy in motivating the efficiency of monetary policy - Libyan economy as a sample -
مقال
Keywords: Monetary Policy, Foreign Exchange Price, Inflation Rate, Libyan Economy.